Jingle eaudiobook - Korman, Gordon (Swindle, 2016)
The eighth installment in #1 New York Times bestselling author Gordon Korman's Swindle series! JINGLE: a light clinking or tingling sounds, often heralding the approach of Santa, reindeer, or the mysterious thief of a priceless possession ... Griffin Bing and his friends are NOT happy. Instead of going away for winter break, they've been signed up to volunteer at a local Christmas extravaganza ... as elves. It's not easy being an elf. Not when Santa is bad news and Rudolph is being played by a Doberman who makes up his own rules wherever he goes. But being an elf is nothing compared to being blamed when a prized Christmas possession—worth over ten million dollars—is stolen right from under your nose. It's time for these elves to get off the shelf and track down a Christmas thief!